Evolution of carbon nanotube dispersion in preparation of epoxy-based composites: From a masterbatch to a nanocomposite - M. Aravand; S. V. Lomov; I. Verpoest; L. Gorbatikh (eXPRESS Polymer Letters)
The state of carbon nanotube (CNT) dispersion in epoxy is likely to change in the process of composite production. In the present work CNT dispersion is characterized at different stages of nanocomposite preparation: in the original masterbatch with high CNT concentration, after masterbatch dilution, in the process of curing and in the final nanocomposite. The evaluation techniques included dynamic rheological analysis of the liquid phases, optical, environmental and charge contrast scanning electron microscopy, electrochemical impedance spectroscopy and dynamic mechanical analysis. The evolution of the CNT dispersion was assessed for two CNT/epoxy systems with distinctly different dispersion states induced by different storage time. Strong interactions between CNT clusters were revealed in the masterbatch with a longer storage time. Upon curing CNT clusters in this material formed a network-like structure. This network enhanced the elastic behaviour and specific conductivity of the resulting nanocomposite, leading to a partial electrical percolation after curing.